Biographical Characteristics, Perception, Motivation and, Job Satisfaction In Lecturer Department Of Dental Nursing Health Polytechnic Of Ministry Of Health Semarang - Bambang Sutomo; Prasko Prasko; Suwarsono Suwarsono (Jurnal LINK, 2014)
The purpose of this study is to determine the effect of biographical characteristics, perceptions of lecturers' functional position, perceptions of the reward system, job motivation rank of career development, and job satisfaction of Lecturer in Dental Nursing Department, Health Polytechnic of Semarang. It is a quantitative research using cross-sectional approach with regression studies. It is a total sampling study where all the population are become the sample. The population and also the sample in this study are 28 lecturers in The Dental Nursing Department Health Polytechnic of Semarang. Correlation analysis was done with Chi Square test (× 2), followed by multiple logistic regression with the method of Backward Stepwise (Likelihood Ratio). Research shows that the majority of lecturers in the category of low satisfaction is 53.8%. Age-related variables are p.value = 0.020, perception allowance p.value = 0.045, perceptions of the reward system p.value = 0.001. Variables that influence the perception of the reward system, p.value = 0.007 and OR (Exp B) = 16.0. It is recommended for the policy makers at the department to plan and implement the reward system to employees.